2018
DOI: 10.3892/or.2018.6941
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CASC2/miR‑18a‑5p axis regulates the malignant potential of nasopharyngeal carcinoma by targeting RBBP8

Abstract: Nasopharyngeal carcinoma (NPC) is a prevalent head and neck tumor which has a high mortality rate in Southeast Asia, especially in Southern China. Cancer susceptibility candidate 2 (CASC2) is a newly identified long non-coding RNA (lncRNA) that has been found to play a suppressive role in several types of tumors. However, the expression and functional role of CASC2 in NPC are still unclear. In the present study, using NPC tissues, cells and transplanted mice, we investigated the mechanism of CASC2-mediated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The research group led by Rose et al suggested that RBBP8 was significantly hypermethylated in bladder cancer (BLCA) and was associated with more prolonged overall survival, and they indicated that it may be used as a complementary marker for the detection of BLCA in urine (Mijnes et al, 2018). Miao et al (2019) reported that the downregulation of the long noncoding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2, enhanced tumor development, increased miR-18a-5p levels, and reduced the expression of RBBP8 in nasopharyngeal carcinoma (NPC). The upregulation of CASC2 resulted in decreased proliferation and increased apoptotic cell death in vivo (Miao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research group led by Rose et al suggested that RBBP8 was significantly hypermethylated in bladder cancer (BLCA) and was associated with more prolonged overall survival, and they indicated that it may be used as a complementary marker for the detection of BLCA in urine (Mijnes et al, 2018). Miao et al (2019) reported that the downregulation of the long noncoding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2, enhanced tumor development, increased miR-18a-5p levels, and reduced the expression of RBBP8 in nasopharyngeal carcinoma (NPC). The upregulation of CASC2 resulted in decreased proliferation and increased apoptotic cell death in vivo (Miao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al (2019) reported that the downregulation of the long noncoding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2, enhanced tumor development, increased miR-18a-5p levels, and reduced the expression of RBBP8 in nasopharyngeal carcinoma (NPC). The upregulation of CASC2 resulted in decreased proliferation and increased apoptotic cell death in vivo (Miao et al, 2019). Our data clearly showed that RBBP8 was differentially expressed and involved in cell cycle regulation (Supplementary Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA cancer susceptibility candidate 2 (CASC2) could inhibit proliferation, induce apoptosis through inhibiting the activation of miR-18a-5p/RB binding protein 8 (RBBP8) axis. 208 MiR-324-3p can inhibit the invasion of tumor cells through its suppression of Homo sapiens GLI family zinc-finger 3 (GLI3) gene expression. 209 High expressions of miR-7 inhibit the , and E-cadherin.…”
Section: Non-coding Rna Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…RBBP8 is located at chromosome 18q11.2 and may be a tumor suppressor 39. Conflicting results have been reported for RBBP8 variants in relation to IA in previous GWASs.…”
Section: Discussionmentioning
confidence: 93%